Osteomodulin attenuates smooth muscle cell osteogenic transition in vascular calcification. Issue 2 (20th February 2022) - Skenteris, Nikolaos T.; Seime, Till; Witasp, Anna; Karlöf, Eva; Wasilewski, Grzegorz B.; Heuschkel, Marina A.; Jaminon, Armand M.G.; Oduor, Loureen; Dzhanaev, Robert; Kronqvist, Malin; Lengquist, Mariette; Peeters, Frederique E.C.M.; et al.
Abstract: Rationale: Vascular calcification is a prominent feature of late‐stage diabetes, renal and cardiovascular disease (CVD), and has been linked to adverse events. Recent studies in patients reported that plasma levels of osteomodulin (OMD), a proteoglycan involved in bone mineralisation, associate with diabetes and CVD. We hypothesised that OMD could be implicated in these diseases via vascular calcification as a common underlying factor and aimed to investigate its role in this context. Methods and results: In patients with chronic kidney disease, plasma OMD levels correlated with markers of inflammation and bone turnover, with the protein present in calcified arterial media. Plasma OMD also associated with cardiac calcification and the protein was detected in calcified valve leaflets by immunohistochemistry. In patients with carotid atherosclerosis, circulating OMD was increased in association with plaque calcification as assessed by computed tomography. Transcriptomic and proteomic data showed that OMD was upregulated in atherosclerotic compared to control arteries, particularly in calcified plaques, where OMD expression correlated positively with markers of smooth muscle cells (SMCs), osteoblasts and glycoproteins. Immunostaining confirmed that OMD was abundantly present in calcified plaques, localised to extracellular matrix and regions rich in α‐SMA + cells. In vivo, OMD was enriched in SMCs around calcified nodules in aortic media of nephrectomised rats and in plaques from ApoE −/− mice on warfarin. In vitro experiments revealed that OMD mRNA was upregulated in SMCs stimulated with IFNγ, BMP2, TGFβ1, phosphate and β‐glycerophosphate, and by administration of recombinant human OMD protein (rhOMD). Mechanistically, addition of rhOMD repressed the calcification process of SMCs treated with phosphate by maintaining their contractile phenotype along with enriched matrix organisation, thereby attenuating SMC osteoblastic transformation. Mechanistically, the role of OMD is exerted likely through its link with SMAD3 and TGFB1 signalling, and interplay with BMP2 in vascular tissues. Conclusion: We report a consistent association of both circulating and tissue OMD levels with cardiovascular calcification, highlighting the potential of OMD as a clinical biomarker. OMD was localised in medial and intimal α‐SMA + regions of calcified cardiovascular tissues, induced by pro‐inflammatory and pro‐osteogenic stimuli, while the presence of OMD in extracellular environment attenuated SMC calcification. Abstract :